2018
DOI: 10.3390/su10020554
|View full text |Cite
|
Sign up to set email alerts
|

The Macroeconomic Determinants of International Casino Travel: Evidence from South Korea’s Top Four Inbound Markets

Abstract: This study investigates the macroeconomic determinants behind the number of foreign visitors to Korean casinos arriving from major source countries, namely Japan, Mainland China, Hong Kong SAR and Taiwan. Using monthly data from 2006 to 2016, we utilized a Structural Vector Autoregression (SVAR) model to investigate the dynamic effects of macroeconomic factors on the number of casino visitors. Estimation results supported the conclusion that visitors from Japan and Mainland China-who account for approximately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…According to the Korea Culture and Tourism Institute (2015), it is briefly estimated that the MERS outbreak caused a decrease in about half of the country's 332 travel agencies, with 1.53 million fewer international visitors compared to June through September of the previous year. In addition, few academic studies have investigated the impacts of the MERS on the tourism industry in Korea (Shi & Li, 2017;Song, 2016;Suh & Kim, 2018). For example, Shi and Li (2017) examined the impact of MERS on the arrival of international tourists from China to Korea.…”
Section: Mers Outbreak and Its Impact On Koreamentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Korea Culture and Tourism Institute (2015), it is briefly estimated that the MERS outbreak caused a decrease in about half of the country's 332 travel agencies, with 1.53 million fewer international visitors compared to June through September of the previous year. In addition, few academic studies have investigated the impacts of the MERS on the tourism industry in Korea (Shi & Li, 2017;Song, 2016;Suh & Kim, 2018). For example, Shi and Li (2017) examined the impact of MERS on the arrival of international tourists from China to Korea.…”
Section: Mers Outbreak and Its Impact On Koreamentioning
confidence: 99%
“…However, little estimation has been conducted related to the impact of epidemics on inbound tourism demand (Song & Lee, 2010), and only a few studies have shown the impact of MERS on inbound tourism using a rigorous methodology (Shi & Li, 2017). Instead, studies have examined the impact of MERS with a particular focus such as on the Chinese tourists to Korea (Shi & Li, 2017); on the number of tourists to Jeju Island (Song, 2016); and on casino visitors to Korea (Suh & Kim, 2018). Although these studies emphasized the negative impact of MERS on the tourism demand, rather less attention has been paid to the overall impact of MERS on Korea's inbound tourism demands using forecasting methods throughout the MERS period.…”
Section: Introductionmentioning
confidence: 99%
“…During the past two decades, as the casino and gaming industries have become mainstream and experienced incredible development (Suh and Kim ), casinos the world over have had to adapt to such rapid growth. At present, the gaming industry is active in the USA, Canada, the Asia Pacific region, Latin America, Europe, the Middle East, and Africa (Kim et al ), and international gaming proceeds are projected to rise due to a particular upsurge in gaming in the Asia Pacific region, especially in Macau and Singapore (Malek and Kim ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Scholars have found antecedents of variables associated with casinos revenues. Suh and Kim () have shown that visitors to casinos are influenced by major macroeconomic variables (e.g. exchange rates, oil prices, stock prices, interest rates, money supply, and exports).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation